2006
DOI: 10.1007/s10869-005-9017-y
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Procedural Justice in Responses to Promotion Decisions

Abstract: This study used structural equations modeling to examine the mediating role of procedural justice in the relationships between promotion decisions and organizational commitment and between promotion decisions and intent to leave the organization. 156 managers and executives in Italian subsidiaries of two large multinational organizations in the chemical industry were surveyed about their career history within the organization and their reactions to promotion decisions over an 8-year period. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 62 publications
2
27
0
6
Order By: Relevance
“…Employees' perceptions of procedural justice in promotion decisions are likely to result in positive perceptions of their organisation and higher levels of organisational commitment (Arvey and Sackett 1993 ;Beehr et al 1980 ;De Souza 2002 ;Halaby and Sobel 1979 ;Lemons and Jones 2001 ). These studies showed a direct relationship between procedural justice and organisational commitment (Bagdadli et al 2006 ;Folger and Konovsky 1989 ;Lemons and Jones 2001 ) and an inverse relationship with intent to leave (Carson et al 1994 ;Porter and Steers 1973 ;Price 1977 ;Stroh et al 1996 ). Pillai et al ( 2001 ) reveal that procedural justice principles may differ as a result of one's individualism versus collectivism orientation.…”
Section: Procedural Justicementioning
confidence: 98%
See 3 more Smart Citations
“…Employees' perceptions of procedural justice in promotion decisions are likely to result in positive perceptions of their organisation and higher levels of organisational commitment (Arvey and Sackett 1993 ;Beehr et al 1980 ;De Souza 2002 ;Halaby and Sobel 1979 ;Lemons and Jones 2001 ). These studies showed a direct relationship between procedural justice and organisational commitment (Bagdadli et al 2006 ;Folger and Konovsky 1989 ;Lemons and Jones 2001 ) and an inverse relationship with intent to leave (Carson et al 1994 ;Porter and Steers 1973 ;Price 1977 ;Stroh et al 1996 ). Pillai et al ( 2001 ) reveal that procedural justice principles may differ as a result of one's individualism versus collectivism orientation.…”
Section: Procedural Justicementioning
confidence: 98%
“…Fairness also infl uences decision acceptance. Organisational fairness in decision-making is likely to augment employees' acceptance and encourage positive reactions to organisational decisions (Bagdadli et al 2006 ). Organisational decisions may include decisions on compensation and b enefi ts (Folger and Konovsky 1989 ), layoffs and terminations (Brockner et al 1994 ), performance appraisals (Greenberg 1986 ;Taylor et al 1995 ) and employee selection processes (Gilliland 1993(Gilliland , 1994Singer 1993 ).…”
Section: Studies On Organisational Justicementioning
confidence: 99%
See 2 more Smart Citations
“…También existen trabajos en los que la justicia se considera variable mediadora entre antecedentes (personales y organizacionales) y diferentes resultados como las actitudes hacia el trabajo ( Elanain, 2009), la percepción de las compensaciones (Bagdadli, Roberson, & Paoletti, 2006;Chi & Han, 2008;Kwon, Kim, Kang, & Kim, 2008), la salud laboral (Wu, Neubert, & Xiang Yi, 2007), la satisfacción (Mossholder, Bennett, & Martin, 1998;Roberson, Moye, & Locke, 1999), el desempeño relacionado con la tarea (Renn, 1998), las conductas desviadas (El Akremi, Vandenberghe, & Camerman, 2010), y las conductas de ciudadanía (Bhal, 2006;Elanain, 2010;Foss et al, 2010;Karriker & Williams, 2009). Algunos trabajos muestran, concretamente, su rol mediador entre diferentes tipos de liderazgo y las conductas de ciudadanía (p. ej.…”
Section: Justicia Organizacional Y Conductas De Compartir Conocimientounclassified